Escola: espaço para a produção de conhecimento - Alves, Lynn Rosalina Gama; Pretto, Nelson (Comunicação & Educação, 1999)
The article discusses the need for the school to reevaluate itself as a space for the production of knowledge since it has paid no attention to the transformations the communication technologies have generated among the new generations. Having access to technology is an important fact for the school, since it is working on the children's cognitive structures and, therefore, requiring changes in the school environment, in the treatment given to the disciplines and to the curricula, so they consider new ways of obtaining information, in order to transform such information into knowledge in a pleasureful manner.